Autoimmune hemolytic anemia after allogeneic hematopoietic stem cell transplantation in adults: A southern China multicenter experience. (10th September 2019) - Lv, Weiran; Qu, Hong; Wu, Meiqing; Fan, Zhiping; Huang, Fen; Xu, Na; Xuan, Li; Lin, Ren; Zhao, Ke; Sun, Jing; Lai, Yongrong; Xu, Yajing; et al.
Abstract: To investigate the incidence and risk factors as well as prognosis of autoimmune hemolytic anemia (AIHA) following allogeneic hematopoietic stem cell transplantation (allo‐HSCT), a total of 1377 adult hematological malignancies at three institutions were enrolled in this study. The 3‐year cumulative incidence of AIHA was 2.2 ± 0.4%. Multivariate analysis showed that haploidentical donors (HRDs) and chronic graft vs host disease (cGVHD) were the independent risk factors for AIHA. Patients with AIHA treated initially with corticosteroids combined with cyclosporine A (CsA) had a higher complete response rate than those with corticosteroids monotherapy (66.7% vs 11.1%; P = .013). The 3‐year cumulative incidence of malignant diseases relapse was 4.4 ± 4.3% and 28.0 ± 1.3% ( P = .013), treatment‐related mortality (TRM) was 8.9 ± 6.3% and 17.4 ± 1.2% ( P = .431), disease‐free survival (DFS) was 56.1 ± 1.5% and 86.7 ± 7.2% ( P = .011), and overall survival (OS) was 86.3 ± 7.4% and 64.1 ± 1.5% ( P = .054), respectively, in the patients with AIHA and those without AIHA. Our results indicate that HRDs and cGVHD are risk factors for AIHA and corticosteroids combined with CsA are superior to corticosteroids as initial treatment for AIHA. Autoimmune hemolytic anemia does not contribute to increase TRM and could reduce the malignant diseases relapse and increase DFS. Abstract : Autoimmune hemolytic anemia (AIHA) occurs more frequently than other autoimmune hematological diseases (AHDs) after allogeneic hematopoietic stem cell transplantation. Haploidentical donors and chronic graft vs host disease are risk factors for AIHA and corticosteroids combined with cyclosporine A are superior to corticosteroids as initial treatment for AIHA. AIHA does not contribute to increase treatment‐related mortality and could reduce the malignant diseases relapse and increase disease‐free survival.